2017
DOI: 10.1021/jacs.7b09224
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of a Unique Polymer That Incorporates a Fluorescent Self-Assembled Metallacycle

Abstract: Despite the well-known anticancer activity of mono- and multi-nuclear platinum complexes, studies of the antitumor performances of platinum-based supramolecular coordination complexes are rare. Herein, we report on the synthesis of a four-armed amphiphilic copolymer Pt-PAZMB-b-POEGMA containing a theranostic metallacycle M, in which the tetraphenylethene derivative acts as an aggregation-induced emissive fluorescent probe for live cell imaging and the 3,6-bis[trans-Pt(PEt3)2]phenanthrene (PhenPt) is an antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(143 citation statements)
references
References 55 publications
0
143
0
Order By: Relevance
“…The hierarchical self-assembly of AIE-based macrocyclesc an be ao ne-pot process when amphiphilic polymers are attached to the Lego blocks. Stang et al synthesized af our-armed amphiphilic copolymer, [67] Pt-PAZMB-b-POEGMA, with metallacyle M, in which the TPE derivativea cts as an AIE functional group for live-cell imaging and phenPt is an anticancer drug ( Figure 28). Under differente xperimentalc onditions, this copolymer can self-assemble into nanoparticles or vesicles to encapsulate anticancer drugs.…”
Section: Coordinating Fluorescent Macrocyclesb Ased On Multiple Lego mentioning
confidence: 99%
“…The hierarchical self-assembly of AIE-based macrocyclesc an be ao ne-pot process when amphiphilic polymers are attached to the Lego blocks. Stang et al synthesized af our-armed amphiphilic copolymer, [67] Pt-PAZMB-b-POEGMA, with metallacyle M, in which the TPE derivativea cts as an AIE functional group for live-cell imaging and phenPt is an anticancer drug ( Figure 28). Under differente xperimentalc onditions, this copolymer can self-assemble into nanoparticles or vesicles to encapsulate anticancer drugs.…”
Section: Coordinating Fluorescent Macrocyclesb Ased On Multiple Lego mentioning
confidence: 99%
“…2C). The NIR-II molecular dye 3 was synthesized from commercially available chemicals, and it was characterized by 1 H NMR, 13 C NMR, and MALDI-TOF-MS (SI Appendix, Figs. S23-S28).…”
Section: Resultsmentioning
confidence: 99%
“…The macrocyclic structure of SCCs can enhance their cellular uptake compared with their corresponding small molecule precursors as well as the binding with biomolecules with high affinity. Our group and others reported that Pt(II) metallacycles-based SCCs can act as anticancer agents or selective sensors for biologically important analytes as well as interact with DNA and proteins (9)(10)(11)(12)(13)(14). However, the poor photostability, low tumor uptake, and limited penetration depth of Pt-based SCCs are challenges to overcome.…”
mentioning
confidence: 99%
“…[12] Their compounds were proposed to accumulate in lysosomes of cancer cells producing low toxicity,yet effectively inducing tumor shrinkage in mouse xenograft models. [13,14] Afurther demonstration of the potential of Pt II -SCCs in biomedicine was provided by Sleiman and Mao,who discovered that Pt II -based metallacycles display fairly good ability to bind DNAG -quadruplexes (G4s) in solution. [13,14] Afurther demonstration of the potential of Pt II -SCCs in biomedicine was provided by Sleiman and Mao,who discovered that Pt II -based metallacycles display fairly good ability to bind DNAG -quadruplexes (G4s) in solution.…”
Section: Introductionmentioning
confidence: 99%